2009
DOI: 10.1002/joc.1951
|View full text |Cite
|
Sign up to set email alerts
|

The impact of El Niño Southern Oscillation phases on off‐season maize yield for a subtropical region of Brazil

Abstract: ABSTRACT:In recent years, maize has become one of the main alternative crops for the autumn-winter growing season in the central-western and southeastern regions of Brazil. However, water deficits, sub-optimal temperatures and low solar radiation levels are common problems that are experienced during this growing season by local farmers. One methodology to assess the impact of variable weather conditions on crop production is the use of crop simulation models. The goal of this study was to evaluate the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
(32 reference statements)
0
12
0
4
Order By: Relevance
“…Brazil is located mainly in the tropical zone with several different climates (Alvares et al, 2013) and presents suitable conditions for production of several profitable crops. However, inter-annual crop yield variability is strongly influenced by El Niño-Southern Oscillation (ENSO) phases (Rodrigues et al, 2011;Zebiak et al, 2015), Pacific decadal oscillation (Kayano and Andreoli, 2007), Atlantic multidecadal oscillation (Kayano et al, 2016), drought intensification (Food and Agriculture Organization of the United Nations (FAO), 2014; Marengo and Torres, 2016), resulting anomalous crop yield losses (Soler et al, 2010;Rolim et al, 2015) and * Correspondence to: P. C. Sentelhas, Department of Biosystems Engineering, ESALQ, University of São Paulo, Av. Pádua Dias, 11, 13418-900 Piracicaba, SP, Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Brazil is located mainly in the tropical zone with several different climates (Alvares et al, 2013) and presents suitable conditions for production of several profitable crops. However, inter-annual crop yield variability is strongly influenced by El Niño-Southern Oscillation (ENSO) phases (Rodrigues et al, 2011;Zebiak et al, 2015), Pacific decadal oscillation (Kayano and Andreoli, 2007), Atlantic multidecadal oscillation (Kayano et al, 2016), drought intensification (Food and Agriculture Organization of the United Nations (FAO), 2014; Marengo and Torres, 2016), resulting anomalous crop yield losses (Soler et al, 2010;Rolim et al, 2015) and * Correspondence to: P. C. Sentelhas, Department of Biosystems Engineering, ESALQ, University of São Paulo, Av. Pádua Dias, 11, 13418-900 Piracicaba, SP, Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…For the year of 2017, it was estimated that 61.3% of the national maize production will come from the off-season growing period (Acompanhamento da Safra Brasileira [de] Grãos, 2017), which is subjected to uncertainties due to climate elements' variability (Soler et al, 2010). In a study using computer modeling, Cardoso et al (2004) found that rainfed maize sowed off-season in northern Paraná state, Brazil, suffers yield breaks and cycle interruption due to lack of rainfall and low temperatures.…”
mentioning
confidence: 99%
“…Los resultados de este artículo también concuerdan con un estudio realizado en Campinas-SP, a 130 km de São-Carlos-SP, donde se evaluaron las precipitaciones de 116 años sin encontrar efecto del cambio climático (Blain et al, 2007). Respecto de los efectos del fenómeno ENOS en el área de estudio, los resultados de este trabajo no concuerdan con el realizado por Soler et al (2010) en los municipios de Piracicaba-SP (años 1917-2002 y Ribeirão Preto-SP (años 1965-2002, a 65 y 85 km de São-Carlos-SP, respectivamente), donde se presentó una relación directa entre las precipitaciones y el fenómeno ENOS.…”
Section: Discussionunclassified
“…Diversos autores han analizado las anomalías producidas por ENOS sobre las precipitaciones en diferentes regiones de Brasil. En el estado de Sao Paulo se ha constatado un aumento en la frecuencia y en la precipitación total de lluvias en los meses de abril y mayo en los años de incidencia de «El Niño» (Nunes, 2000;Soler et al, 2010).…”
unclassified